Analysis of the impacts of the System for Registration and Monitoring of Hypertensive and Diabetic Patients (HIPERDIA) and the Mais Médicos program on hospitalizations and deaths due to heart failure in Pará between 1984 and 2022 (Research, Society and Development, 2025)
Heart failure (HF) is a prevalent chronic condition and a significant public health challenge, characterized by the heart's inability to pump blood effectively. This study aims to analyze the impacts on the Brazilian Unified Health System (SUS) of the Registration and Monitoring System for Hypertensive and Diabetic Patients (HIPERDIA) and the Mais Médicos program regarding hospitalization and mortality rates due to heart failure in the state of Pará, from 1984 to 2022. Primary Health Care (PHC), as the preferred entry point to SUS, is essential for early detection of risk factors, continuous follow-up, and prevention of complications. The HIPERDIA program, implemented in 2002, aims to control hypertension and diabetes, having a strong impact on HF prevention. The Mais Médicos program, created in 2013, expanded PHC coverage in remote regions of the Amazon. This is an ecological, retrospective, and quantitative study based on data from 1984 to 2022. A significant decrease in HF mortality was observed, from 15.51 to fewer than 10 deaths per 100,000 inhabitants, along with a stabilization of hospitalizations below 100 per 100,000 starting in 2008. Despite this, absolute deaths increased from 664 (2013) to 844 (2022). It is concluded that strengthening PHC contributes to early HF management, reduced hospitalizations, and improved quality of life for patients.